Fischer Type Log-Majorization of Singular Values on Partitioned Positive Semidefinite Matrices. (31st August 2021) - Wang, Benju; Zhang, Yun
Abstract : In this paper, we establish a Fischer type log-majorization of singular values on partitioned positive semidefinite matrices, which generalizes the classical Fischer's inequality. Meanwhile, some related and new inequalities are also obtained.